2018
DOI: 10.3390/brainsci8080149
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Immunological Data for Precise Classification of OCD Patients

Abstract: Obsessive–compulsive disorder (OCD) affects about 2% of the general population, for which several etiological factors were identified. Important among these is immunological dysfunction. This review aims to show how immunology can inform specific etiological factors, and how distinguishing between these etiologies is important from a personalized treatment perspective. We found discrepancies concerning cytokines, raising the hypothesis of specific immunological etiological factors. Antibody studies support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 184 publications
0
17
0
Order By: Relevance
“…Recent research has shown that dopamine levels may contribute to the immunological mechanisms involved in PANDAS pathogenesis [109][110][111]. Altered levels of dopamine may also be an explanation of the decrease of Treg levels and elevations in proinflammatory cytokines [112][113][114][115]. Moreover, it was observed that among PANDAS patients, vitamin D deficiency was significantly more frequent in comparison to the control groups [78].…”
Section: The Pathophysiology Of Gas Infection and Pandasmentioning
confidence: 99%
“…Recent research has shown that dopamine levels may contribute to the immunological mechanisms involved in PANDAS pathogenesis [109][110][111]. Altered levels of dopamine may also be an explanation of the decrease of Treg levels and elevations in proinflammatory cytokines [112][113][114][115]. Moreover, it was observed that among PANDAS patients, vitamin D deficiency was significantly more frequent in comparison to the control groups [78].…”
Section: The Pathophysiology Of Gas Infection and Pandasmentioning
confidence: 99%
“…Nevertheless, up to half of all OCD patients do not benefit from this combination treatment in a clinically meaningful way [ 6 ], which has prompted efforts aimed at identifying diagnostic subgroups with specific pathogenic mechanisms that may mediate treatment resistance, as well as improving treatment options. In this line, a subgroup of patients may have a secondary form of OCD with an organic cause, which often appears to be autoimmune mediated [ 19 , 24 26 ]. In the novel ICD-11 criteria, reflecting DSM-5 nosology, this aspect is taken into account by introducing the category “secondary OCD or related syndrome” ( https://icd.who.int ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these genetic and epidemiological findings, there is an emerging body of preliminary data that is focused on inflammatory markers (cytokine and immunoglobulin levels), immune cell populations, and gene expression profiling of peripheral lymphocytes. These data indicate some degree of hyperactivity of both the innate and the adaptive immune systems in TS, childhood-onset OCD and ADHD [131][132][133][134][135] .…”
Section: Stress Neuroinflammation Maternal Immune Activation and Tmentioning
confidence: 72%